Iowa RBA, February 19, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for February 19, 1996. Highlights of the update include sightings of a Great Gray Owl, Snowy Owl, White-winged Crossbill, and Hoary Redpolls. Also included are handwritten notes for the next week's update with sightings of a Peregrine Falcon and a Snow Goose. Epson - sheet feed/flatbed